ANALISIS PENGUASAAN KONSEP AWAL FISIKA PADAPEMBELAJARAN MENGGUNAKAN MODEL ADVANCE ORGANIZER BERBASIS EKSPERIMEN TERHADAP HASIL BELAJAR FISIKA - Ramlan Sungkawan; Motlan . (Jurnal Pendidikan Fisika, 2013)
This study was aimed to determine the differences between: (1) student’s study result of using advance organizer Model and direct instruction model and (2) student’s study result who at first have low or highcomprehension in physical concept. (3) The relation between advanceorganizer model and direct instruction model to develop student study interestin physics. This is quasi experimental research which students of secondsemester of grade X SMK N 1 Pantai Labu Deli Serdang as a populationchose random sample of each class. The instrument that is used: (1) test forfirst comprehension of concept (2) test for study result which “DynamicPower” as a basic material. The test is used to obtain the data is form of essay.And the data were collected in essay and analyzed according to ANAVA. Itshows that: (1) there are the different between students’ study results that useadvance organizer and direct instruction. (2) There are the differencesbetween students’ study results that have low or high skill in advanceorganizer or Direct Instruction class.  (3) There is no interaction between theusing learning of advance organizer or direct Instruction and the degree ofconcept comprehension to develop students’ study result.